Relationship Between The Endophytic Bacteria Pseudomonas Aeruginosa Isolated From Medicinal Plants And The Production Of Bioactive Compounds (Journal of Namibian Studies : History Politics Culture, 2022)
Rice is one of the most important foods in the family basket. In recent years, rice has shown a decrease in its production due to diseases that have caused great economic losses. To control diseases, the application of agrochemicals is necessary. As an alternative to replace agrochemicals, we have opted for the application of beneficial microorganisms which confers protection against pathogens and favors plant growth.is necessary to search for beneficial microorganisms capable of controlling phytopathogens that cause diseases in crops, in order to replace the application of agrochemicals which cause environmental problems. Evaluate the antagonistic activity in vitro of Pseudomonas aeruginosa against Burkholderia glumae. The morphotypes isolated from Lippia origanoides were used, which were activated and purified in R2A medium. Each morphotypes was inoculated in 3s medium for 7 days for the production of secondary metabolites. After the time, we proceeded to concentrate the bacterial extract and evaluate it on filter paper discs in culture medium King B previously plated with pathogens. Likewise, the morphotypes were molecularly identified from the 16S rRNA gene. An analysis of variance and the Duncan multiple range test were applied for the inhibitory activity of morphotypes against pathogens. To phylogenetic analyses, the morphotypes evaluated showed 100% homology with Pseudomonas aeruginosa. In addition, they had the ability to control the growth of pathogens by releasing secondary metabolites. This species is characterized by producing secondary metabolites that control the growth of pathogens. The application of beneficial microorganisms with antagonistic potential may become in the future a great alternative to replace the application of agrochemicals.